Methodology for determining the availability of natural moistening of the territory by hydrometeorological conditions for the needs of land reclamation - Tkachuk, Andriy; Ткачук, Андрій Васильович; Tkachuk, Tetyana; Ткачук, Тетяна Іванівна (IOP Publishing Ltd, 2023)
The paper considers one of the important problems of water use – determination of the humidification conditions of the territory for the hydromelioration needs. The methodical approach to determining the probability of exceeding natural moisture by a group of criteria is highlighted. Nowadays there is no single, reliable and simple method for determining this indicator. Assessing climatic conditions, considering their impact on crop productivity, it is necessary to take into account hydrometeorological factors that have a decisive influence on the development of crops and, accordingly, determine their yield. These include, first of all, precipitation, moisture reserves in the soil, evapotranspiration and other complex indicators that allow to take into account the distribution of meteorological factors during the growing season of the crop and their possible negative impact on the development of the plant, because each crop requires a certain optimal regime of soil temperature and moisture at different stages of its development. The article presents the solution of the set tasks on the example of winter wheat crops according to the data of the Dnipro meteorological station (airport). У роботі розглядається одна з важливих проблем водокористування – визначення умов зволоження території для потреб гідромеліорації. Висвітлено методичний підхід до визначення ймовірності перевищення природної вологості за групою критеріїв. На сьогоднішній день не існує єдиного, надійного і простого методу визначення цього показника. Оцінюючи кліматичні умови, враховуючи їх вплив на продуктивність сільськогосподарських культур, необхідно враховувати гідрометеорологічні чинники, які мають визначальний вплив на розвиток сільськогосподарських культур і, відповідно, визначають їх урожайність. До них, насамперед, відносяться опади, запаси вологи в ґрунті, випаровуваність та інші комплексні показники, які дають змогу врахувати розподіл метеорологічних факторів протягом вегетаційного періоду культури та їх можливий негативний вплив на розвиток рослини, адже кожна культура потребує певного оптимального режиму температури і вологи ґрунту на різних етапах її розвитку. У статті наведено рішення поставлених завдань на прикладі посівів озимої пшениці за даними Дніпровської метеостанції (аеропорту).
Методика визначення забезпеченості природного зволоження території гідрометеорологічними умовами для потреб меліорації
Keywords: melioration; меліорація; natural moistening of the territory; природне зволоження території; hydrometeorological conditions; гідрометеорологічні умови